Investigation of Bubble Breakup in Venturi-Type Microbubble Generator with Twisted Baffle - Rifda Salsabila Zahra; Sigit Deddy Purnomo Sidhi; Deendarlianto Deendarlianto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The microbubble generator is an essential technology in various applications, such as water treatment, due to its ability to improve mass transfer efficiency, particularly ocygenation. Bubble breakup is a critical process that affects bubble size and its distribution in the solution, In this study, the experimental investigation focuses on analyzing the bubble breakup phenomenon in a venturi-type microbubble generator (MBG) equipped with a twisted baffle. Water flow rates and air flow rates ) were varied at = 40 and 60 lpm and = 0,2 and 0,6 lpm. The methods used in this study include visualizing the bubble breakup process using a high-speed camera and measuring pressure fluctuations in the MBG detected by a pressure transducer. The analysis involves Power Spectral Density (PSD), Probability Density Function (PDF) of pressure drop, and Discrete Wavelet Transform (DWT). The tests were conducted with variations in water and air flow rates, as well as pressure measurements to understand the interaction between liquid and gas flows. The analysis results indicate that the presence of the twisted baffle significantly increases flow turbulence, which accelerates the bubble breakup process. This process produce smaller and more evenly distributed bubbles, which is crucial for enchancing dissolved ocygen (DO) levels in the solution.